Perendaman Bunga Potong Gerbera (Gerbera jamesonii) dalam Campuran Larutan Air Kelapa dan Ekstrak Belimbing Wuluh untuk Memperpanjang Vase Life - NI LUH ASRI PRADNYANI; I MADE SUKEWIJAYA; I NYOMAN GEDE ASTAWA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2022)
Soaking Gerbera Cut Flowers (Gerbera jamesonii) in a Mix of Coconut Water Solution and Wuluh Starfruit Extract to Extend Vase Life Gerbera is a flowering ornamental plant that is used as cut flowers and has high economic and aesthetic value. Gerbera flowers are often damaged such as wilting, easily broken stems, broken buds and flower discoloration. The very short shelf life of cut gerbera flowers requires proper postharvest handling to maintain freshness. This research aims to determine the effect of coconut water (Cocos nucifera) and wuluh starfruit (Averrhoa bilimbi) extract and its interaction in increasing vase life and to determine the best soaking solution dose for gerbera cut flowers. The research used a Completely Randomized Design consisting of two factors, that is coconut water with doses of K1: 40 ml, K2: 60 ml, and K3: 80 ml, and wuluh starfruit extract with doses of B1: 10 ml, B2: 20 ml, and B3: 30 ml, there were 9 treatment combinations and each treatment was repeated three times. The results showed that the interaction between coconut water and wuluh starfruit extract had a significant effect on the solution acidity and vase life variables. Treatment of 80 ml coconut water + 10 ml star fruit extract (K3B1) was able to maintain the appearance of gerbera cut flowers in a vase up to 13,83 days.